Simulation in Nursing Education: Review of Research - Ghimire, Sulochana; Kachapati, Anuja (Journal of Universal College of Medical Sciences, 2020)
INTRODUCTION Nursing education consists of the theoretical and practical training provided to nurses with the purpose to prepare them for their duties as nursing care professionals. The scope of nursing practice reflects all the role and responsibilities undertaken by the nurse to address the full range of human experiences and responses to health and illness. The instructional strategies utilized in both didactic and clinical components of nursing education courses are highly influential in determining critical thinking and clinical decision making ability as well as in developing the psychomotor skill performance of new graduates. Simulation provides nursing students with opportunities to practice their clinical and decision-making skills through various real-life situational experiences. Although endorsed in nursing curricula, its effectiveness is largely unknown.